Swelling Behaviour of a Novel Protein-Based Super Absorbent Hydrogel Composed of Poly(methacrylic Acid) and Collagen - Sadeghi, Mohammad; Hosseinzadeh, Hossein (Asian Journal of Chemistry, 2010)
In this paper, a novel protein-based super absorbent hydrogel was synthesized through crosslinking graft copolymerization of methacrylic acid onto collagen, using ammonium persulphate as a free radical initiator in the presence of methylenebisacrylamide as a crosslinker. The hydrogel structure was confirmed by FTIR spectroscopy. We were systematically optimized the certain variables of the graft copolymerization (i.e., the monomer, the initiator and the crosslinker concentration) to achieve a hydrogel with maximum swelling capacity. Under the optimized conditions concluded, maximum capacity of swelling in distilled water was found to be 415 g/g. The swelling kinetics of the synthesized hydrogels with various particle sizes was preliminarily investigated. Absorbency in aqueous chloride salt solutions indicated that the swelling capacity decreased with an increase in the ionic strength of the swelling medium. The swelling of super absorbing hydrogels was also measured in solutions with pH ranged from 1-13. The synthesized hydrogel exhibited a pH-responsiveness character so that a swelling-collapsing pulsatile behaviour was recorded at pHs 2 and 7. This behaviour makes the synthesized hydrogels as an excellent candidate for controlled delivery of bioactive agents.